Pentingnya Pengetahuan Kesehatan Reproduksi pada Remaja - Ika Choirin Nisa; Ela Rohaeni; Rif’atun Nisa; Iis; Iis Aisah; Abel Paramisti (Rena Cipta Mandiri, 2025)
Adolescence is a transitional period from childhood to adulthood characterized by biological, emotional, social, and cognitive changes. During this period, adolescents’ reproductive organs begin to function actively, making them a vulnerable age group to various reproductive health problems, such as unintended pregnancy, sexually transmitted infections, and early marriage. These problems are often influenced by adolescents’ low level of knowledge regarding reproductive health. Adolescent reproductive health refers to a healthy condition related to the reproductive system, functions, and processes, encompassing physical, mental, social, and cultural aspects. Therefore, maintaining reproductive health during adolescence is very important as a preventive effort against future health risks. The purpose of this counseling activity was to increase and enhance adolescents’ knowledge of reproductive health. The method used was health education through interactive counseling. Based on the results of a self-assessment survey, it was found that the main problem was a lack of reproductive health knowledge among 30 adolescents. To address this issue, counseling was conducted covering the definition of reproductive health, common reproductive health problems, and ways to maintain reproductive health. After the counseling session, participants showed high enthusiasm for the material presented through leaflets and video media.